ANALISIS EFEKTIVITAS PENYALURAN ZAKAT PADA BAZNAS KABUPATEN LANGKAT - Salsabilla Siagian; Marliyah Marliyah (IAIN Lhokseumawe, 2021)
National Amil Zakat Agency (BAZNAS) Kab. Langkat is an official management institution where the management is determined based on the Decree of the Regent of Langkat. This study aims to measure the effectiveness of BAZNAS zakat funds in Langkat Regency. The method used in this study is a qualitative method with a descriptive approach. Measuring the effectiveness of zakat funds using the Zakat Core Principle (ZCP) measurement ratio. The object used in this study is the financial statements of BAZNAS from 2016 to 2020. The results show that the average amount of ZIS collection for the last 5 years is Rp. 1,476,762,640. While the total sales of ZIS for the last 5 years amounted to Rp 1,058,966,407. Based on ZCP, the effective rate for the last 5 years of operation is 72%. This shows that the level of effectiveness is included in the Effective category, the Allocation to Collection Ratio (ACR) reaches 70-89 percent.